(untitled) (Physical Education, Health and Social Sciences, 2026)
Aquatic contamination by pesticides such as buprofezin poses a serious threat to freshwater organisms, leading to toxicity and oxidative stress. This study evaluated the toxicological impact of buprofezin on Cyprinus carpio using enzymatic biomarkers as indicators of oxidative imbalance. Fish were exposed for 96 hours to three concentrations: T0 (control, 0 mg L⁻¹), T1 (5 mg L⁻¹), and T2 (10 mg L⁻¹). Oxidative stress responses were assessed through Catalase (CAT), Superoxide Dismutase (SOD), and Glutathione-S-transferase (GST) activities in hepatic and renal tissues. A clear dose-dependent increase in all enzymatic biomarkers was observed. In the liver, CAT activity increased significantly (P = 0.032), rising from 1156.65 UmL⁻¹ in controls to 1359.41 UmL⁻¹ in T2, while hepatic SOD showed a marked elevation from 234.75 UmL⁻¹ (control) to 520.31 UmL⁻¹ in T2 (P = 0.011). Hepatic GST activity also rose significantly (P = 0.021), with values increasing from 878.55 UmL⁻¹ (control) to 1407.19 UmL⁻¹ in T2, confirming enhanced detoxification activity. Similar trends occurred in renal tissues. Renal CAT increased significantly (P = 0.017), from 701.65 UmL⁻¹ in controls to 944.41 UmL⁻¹ in T2, while renal SOD rose from baseline levels to 403.73 UmL⁻¹ in T2 (P = 0.018). Renal GST also showed a strong dose-response pattern (P = 0.022), increasing from 756.05 UmL⁻¹ (control) to 1508.60 UmL⁻¹ in T2, indicating intensified conjugation and detoxification processes. Overall, the pronounced elevation of CAT, SOD, and GST in both liver and kidney demonstrates that buprofezin induces significant oxidative stress, activating compensatory antioxidant mechanisms in Cyprinus carpio. The magnitude of enzymatic responses was strongly dose-dependent, with the highest concentration (10 mg L⁻¹) producing the most severe oxidative challenge. These findings highlight the ecological risks of buprofezin contamination in aquatic environments and emphasize the importance of strict monitoring and regulation to protect freshwater biota.